High-exposure-ratio {010} active surface O2 type cobalt-based layered oxide as well as preparation method and application thereof
Through co-precipitation method and low-temperature ultrasonic liquid-phase ion exchange reaction, the exposure ratio of the {010} active surface of O2-type cobalt base oxide was regulated, which solved the problem of poor energy density and rate performance of existing materials, and achieved the improvement of high energy density and power density.
Patent Information
- Application Number
- CN202510117294.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
AI Technical Summary
The energy density, rate performance and cycle stability of the existing O2-type cobalt-based oxides are poor, and it is difficult to increase the exposure ratio of the active surface by increasing the lithium ion diffusion channel.
Cobalt-based hydroxide precursors were prepared by co-precipitation method, and their particle shape and size were regulated to increase the {010} crystal surface area. Subsequently, sodium source was introduced and sodium-embedded cobalt-based layered oxide was prepared by high-temperature calcination, and finally the {010} active surface exposure ratio was increased by low-temperature ultrasonic liquid-phase ion exchange reaction.
It significantly improves Li⁺ transmission dynamics, improves the energy density and power density of O2 cobalt-based cathode materials, enhances cycling stability, and meets the needs of high-performance lithium-ion batteries.
Smart Images

Figure CN119911979A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery positive electrode material preparation, and specifically relates to a high exposure ratio {010} active surface O2 type cobalt-based layered oxide and a preparation method and application thereof. Background Art
[0002] Since its introduction in 1982, O2-type layered lithium cobalt oxide has not been commercially applied due to its complex preparation process, but its unique facet-sharing structure gives it excellent structural stability and high-voltage cycling performance. In the O3-type layered lithium cobalt oxide structure, lithium ions diffuse from the center of a LiO6 octahedron to the adjacent tetrahedral vacancy and then to the center of the adjacent octahedral vacancy, where the tetrahedral vacancy is coplanar with the CoO6 octahedron in the [CoO2] cobalt layer. In contrast, in O2-type layered lithium cobalt oxide, because the LiO6 octahedron is coplanar with the CoO6 octahedron in the [CoO2] layer on one side and coplanar on the other side, half of the tetrahedral vacancies in the [LiO2] layer are coplanar with the CoO6 octahedron, and the other half of the tetrahedral vacancies are coplanar with the tetrahedral vacancies in the [CoO2] layer. Therefore, lithium ions diffuse through the tetrahedral vacancies on the coplanar sides of the LiO6 and CoO6 octahedra in the O2-type layered structure, resulting in a significant reduction in the diffusion energy barrier.
[0003] The {010} active surface is a crystal surface with high catalytic activity and specific physical and chemical properties in crystalline materials. Its exposure ratio and state have an important influence on the catalytic activity, stability, ion transport performance and other aspects of the material. Especially in battery materials, the exposure ratio of the {010} active surface also has an important influence on the ion transport performance. For example, in secondary batteries such as lithium-ion batteries and sodium-ion batteries, positive electrode materials with highly exposed {010} active surfaces often exhibit higher ion diffusion coefficients and better rate performance. This is because the {010} active surface may provide more ion transport channels, promoting the rapid diffusion and transport of ions. Therefore, by regulating the conditions during the synthesis process, the exposure ratio and state of the {010} active surface can be optimized, thereby improving the performance of the material. This is of great significance for the development of new functional materials and improving the performance of existing materials.
[0004] However, there have been no reports on the regulation of the {010} active surfaces of O2-type cobalt-based hierarchical oxides, resulting in relatively poor energy density, rate performance and cycle stability of existing O2-type cobalt-based hierarchical oxides. Therefore, how to improve the lithium ion diffusion channel, that is, increase the exposure ratio of the {010} active surface, still faces huge challenges. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high exposure ratio {010} active surface O2-type cobalt-based layered oxide and its preparation method and application, so as to solve the technical problems of low energy density, poor rate performance and cycle performance of the prior art O2 layered lithium cobalt oxide materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide, comprising: Firstly, a cobalt-based hydroxide precursor is prepared by a coprecipitation method. In this process, the particle shape and size of the cobalt-based hydroxide precursor are adjusted to control the growth in the thickness direction of the wafer, thereby obtaining a cobalt-based hydroxide precursor with a large {010} crystal plane area. Then, a sodium source is introduced and a sodium-intercalated cobalt-based layered oxide is prepared by a high-temperature calcination method; Finally, the sodium-embedded cobalt-based layered oxide and lithium salt solution were subjected to a low-temperature ultrasonic liquid-phase ion exchange reaction to prepare a cobalt-based layered oxide with a high exposure ratio of {010} active surface O2.
[0007] Specifically, the method for preparing the above-mentioned high exposure ratio {010} active surface O2-type cobalt-based layered oxide comprises the following steps: Step 1. Precursor preparation The inorganic or organic salt of cobalt and the inorganic or organic salt of sodium are used as the main raw materials, and organic and inorganic salts of different metal elements are added to prepare the hydroxide precursor Co by coprecipitation method. x M 1-x (OH)2 (M = Al, Ni, Mn, Ti, Fe, Zn and other 3d transition metal elements), regulate the particle shape and size of the hydroxide precursor, control the growth in the thickness direction of the chip, and obtain a hydroxide precursor with a large {010} crystal plane area. Different chip sizes and secondary particles of different sizes can be obtained. The chip length range is 0.5~2μm, the chip width range is 0.1~0.5 μm, and the size range of the secondary particles is 7~15 μm.
[0008] Preferably, the specific operation process of this step is: under an inert gas atmosphere, cobalt salt, other metal salts, precipitant and complexing agent are added dropwise to a reactor containing a certain amount of deionized water at a certain speed, wherein the dropping speed of cobalt salt, other metal salts and precipitant is 0.5-5.0 ml / min, the pH value in the reactor is controlled to be 10.5-12.5, the ammonia concentration in the reactor is controlled to be 0.1-1.0 mol / L, and the reaction is carried out at a temperature of 40-60°C for 30-60 hours to obtain hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor.
[0009] Furthermore, in the operation process of the coprecipitation method described in step 1 above, the precipitant is a NaOH solution, the complexing agent is an ammonia solution, the molar concentration of the cobalt salt is 1.0 to 3.0 mol / L, the molar concentration of the precipitant is 2.0 to 6.0 mol / L, and the molar concentration of the complexing agent is 1.0 to 15.0 mol / L.
[0010] Furthermore, in the above step 1, during the drying operation, the temperature is 90 to 120° C. and the drying time is 20 to 30 h.
[0011] Step 2. High temperature calcination.
[0012] The layered ordered oxide NaCo was prepared by calcining the above precursor at high temperature. x M 1-x O2 (M = Al, Ni, Mn, Ti, Fe, Zn, etc.), the flaky particles have a length distribution range of 0.3 to 12 μm and a thickness distribution range of 0.5 to 5 μm.
[0013] Preferably, the specific operation is: according to the chemical formula NaCo x M 1-x O2 ratio, take the sodium source and the precursor obtained in step 1), mix them evenly, and then pre-sinter them at 400-600°C for 2-8 h in an oxygen atmosphere, and then calcine them at 700-1000°C for 1-30 h, and naturally cool them to room temperature to obtain a layered ordered oxide NaCo x M 1-x O2 (M = Al, Ni, Mn, Ti, Fe, Zn, etc.), where 0.0 ≤ x ≤ 0.2.
[0014] Further preferably, in the above step 2, the sodium source is Na2CO3 or NaOH.
[0015] Further preferably, in the above step 2, the sintering system is: starting from room temperature, heating to 400-600°C at a heating rate of 3-10°C / min, pre-burning for 2-8 h, and then calcining at 700-900°C for 5-25 h.
[0016] Step 3. Ion exchange The cobalt-based layered oxide prepared in step 2 is mixed with a lithium salt solution with a concentration of 0.5 to 10 mol / L, and subjected to ultrasonic treatment for about 0.5 to 10 h at a reaction temperature of 80 to 100 °C, and then filtered, washed and dried to obtain O2-type LiCo x M 1-xO2 (M = Al, Ni, Mn, Ti, Fe, Zn, etc.) materials. This method can obtain layered hydroxide materials with different morphologies and particle sizes by adjusting the reaction conditions in the precursor preparation stage, thereby further obtaining O2-type cobalt-based layered oxides with high exposure ratio {010} active surfaces.
[0017] Furthermore, in the above step 3, the lithium salt is LiNO3, LiCl, LiOH·H2O or LiCH3COO.
[0018] Furthermore, in the above step 3, the solvent of the lithium salt solution is water or ethanol.
[0019] Furthermore, in the above step 3, the layered oxide NaCo x M 1-x The molar ratio of O2 to sodium and lithium in the lithium salt solution is 1: (1 to 10).
[0020] Furthermore, in the above step 3, during the drying operation, the temperature is 100 to 120° C. and the drying time is 8 to 25 hours.
[0021] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a high exposure ratio {010} active surface O2-type cobalt-based hierarchical oxide LiCo x M 1-x The preparation method of O2 (M = Al, Ni, Mn, Ti, Fe, Zn, etc.) is to first directly prepare a hydroxide precursor by coprecipitation, and adjust the particle shape, particle size and preferred growth direction of the hydroxide precursor to obtain a hydroxide precursor with a high proportion of {010} crystal planes; then, the sodium-containing layered oxide NaCo is calcined at high temperature. x M 1-x O2 (M = Al, Ni, Mn, Ti, Fe, Zn, etc.), and then use the liquid phase ion exchange method to evenly mix the prepared sodium-embedded layered oxide with an appropriate amount of lithium salt solution, and perform ion exchange reaction under ultrasound at low temperature. After filtering, washing and drying, the O2-type cobalt-based layered oxide is obtained. This method can prepare sodium-embedded cobalt-based layered oxides with a high exposure ratio {010} active surface by regulating the coprecipitation process conditions and high-temperature sintering process parameters, thereby further preparing O2-type cobalt-based lithium-embedded layered oxides with a high exposure ratio {010} active surface. The layered positive electrode material prepared by this method has excellent electrochemical properties, uniform particle distribution, controllable particle size, good batch uniformity, and the method is simple in process, easy to operate, and the material structure is stable and reliable.
[0022] The present invention can prepare cobalt-based layered positive electrode materials with different primary particle sizes. The prepared primary particles are all micron-sized particles, and the primary particle {010} crystal surface area is large, which can well meet the requirements of downstream lithium-ion battery manufacturers for high energy density and high power density of materials. The preparation process is simple, the process cost is low, and it has excellent cycle stability. It can be widely used in portable electronic products such as mobile phones and laptops and power vehicle markets. The experimental results show that the layered structure lithium-ion battery positive electrode material prepared by the method of the present invention has excellent cycle performance. Under the conditions of 3.0-4.6 V and 10C, the capacity retention rate of the material after 100 cycles is still as high as 80% or more, which can be widely used in the electronic products and power vehicle markets. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the cobalt hydroxide precursor prepared in Example 2 of the present invention; Figure 2 This is an X-ray diffraction pattern of the cobalt hydroxide precursor prepared in Example 3 of the present invention; Figure 3 This is a scanning electron microscope image of the P2-type sodium-cobalt-embedded layered oxide prepared in Example 4 of the present invention; Figure 4 This is a scanning electron microscope image of the cobalt hydroxide precursor prepared in Example 4 of the present invention; Figure 5 This is an X-ray diffraction pattern of the cobalt hydroxide precursor prepared in Example 4 of the present invention; Figure 6 The first cycle charge and discharge curve of the O2-type layered cathode material prepared in Example 4 of the present invention at a rate of 10C; Figure 7 This is a scanning electron microscope image of the P2-type sodium-cobalt-embedded layered oxide prepared in Example 5 of the present invention; Figure 8 The cycle performance curve of the O2-type layered cathode material prepared in Example 5 of the present invention at a rate of 10C; Fig. 9 This is a scanning electron microscope image of the O2-type layered positive electrode material prepared in Example 6 of the present invention; Fig.10 The first cycle charge and discharge curve of the O2-type layered cathode material prepared in Example 6 of the present invention at a rate of 20C; Fig.11 This is a scanning electron microscope image of the O2-type layered positive electrode material prepared in Example 7 of the present invention; Fig.12 The rate performance curve of the O2-type layered cathode material prepared in Example 7 of the present invention at 4.6 V; Fig.13This is the cycle performance curve of the O2-type layered positive electrode material prepared in Example 7 of the present invention at a rate of 20C. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings: Example 1 The positive electrode material prepared in this embodiment is LiCoO2.
[0027] A method for preparing O2-type LiCoO2 with a high exposure ratio of {010} active surface comprises the following steps: Step 1. Coprecipitation Cobalt sulfate solution was prepared according to the chemical formula Co(OH)2, wherein the molar concentration of cobalt sulfate was 3.0 mol / L, the molar concentration of NaOH solution was 2.0 mol / L, and the molar concentration of ammonia solution was 5.0 mol / L. Cobalt sulfate and NaOH were added dropwise to the reactor under a nitrogen atmosphere at a rate of 3.0 ml / min, the pH value in the reactor was controlled to be 11, the ammonia concentration in the reactor was controlled to be 0.2 mol / L, and the reaction was carried out at 40°C for 30 hours to obtain hydroxide slurry, which was then washed and dried to obtain a precursor.
[0028] Step 2. High temperature calcination According to the ratio of the chemical formula NaCoO2, Na2CO3 and the precursor Co(OH)2 obtained in step 1) are mixed evenly, pre-calcined at 400°C for 4 h in an oxygen atmosphere, and then calcined at 700°C for 30 h. The mixture is naturally cooled to room temperature to obtain a layered ordered oxide NaCoO2.
[0029] Step 3. Ion exchange: The NaCoO2 prepared in step 2) is evenly mixed with a 0.5 mol / L LiNO3 aqueous solution, and ultrasonicated at a reaction temperature of 80°C for about 5 h, wherein the sodium-lithium molar ratio of NaCoO2 to the lithium salt solution is 1:(1-10). After the reaction is completed, the reaction system is filtered, the filter cake is washed with deionized water, and dried at 100°C for 20 h. The obtained product is collected to obtain O2-type LiCoO2 material.
[0030] The charging and discharging performance test process of the positive electrode material prepared in this embodiment is as follows: A certain amount of the positive electrode material prepared in this embodiment, acetylene black, and binder polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1:1, added to N-methylpyrrolidone (NMP) to prepare a slurry, wherein the content of NMP is 30 times that of PVDF, and evenly coated on an aluminum foil. The mixture was vacuum dried at 80° C. for 12 hours, and then cut into pole pieces with a diameter of 12 mm using a mold. A metal lithium sheet was used as a negative electrode, a Celgard 2400 commercial polypropylene film was used as a separator, and an electrolyte was LP30. The mixture was assembled into a button cell of model CR2032 in a glove box filled with an inert gas.
[0031] Charge and discharge performance test: The O2-phase layered cathode material LiCoO2 prepared in this example was tested at a voltage range of 3.0 to 4.6 V and 0.5C, and the first charge and discharge capacities were 220.2 mA h / g and 216.8 mA h / g, respectively.
[0032] Example 2 The positive electrode material prepared in this embodiment is LiCo 0.96 Al 0.04 O2.
[0033] A method for preparing O2-type LiCo with high exposure ratio {010} active surface 0.88 Al 0.12 The preparation method of O2 comprises the following steps: Step 1. Coprecipitation According to the chemical formula Co 0.88 Al 0.12Cobalt sulfate and aluminum sulfate solution are mixed in a ratio of (OH)2, wherein the molar concentration of cobalt sulfate is 3.0 mol / L, the molar concentration of aluminum sulfate solution is 0.3 mol / L, the molar concentration of NaOH solution is 2.0 mol / L, and the molar concentration of ammonia solution is 5.0 mol / L. In a nitrogen atmosphere, cobalt sulfate, lithium sulfate and NaOH are added dropwise to a reactor at a rate of 3.0 ml / min, the pH value in the reactor is controlled to be 11.5, the ammonia concentration in the reactor is controlled to be 0.2 mol / L, and the reaction is carried out at 40°C for 30 hours to obtain a hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor.
[0034] Step 2. High temperature calcination According to the chemical formula NaCo 0.88 Al 0.12 O2 ratio, take Na2CO3 and the precursor Co obtained in step 1) 0.88 Al 0.12 (OH)2, mixed evenly, pre-calcined at 400 °C for 4 h in an oxygen atmosphere, calcined at 1000 °C for 1 h, and naturally cooled to room temperature to obtain a layered ordered oxide NaCo 0.96 Al 0.04 O2.
[0035] Step 3. Ion exchange: The NaCo prepared in step 2) 0.88 Al 0.12 O2 was mixed evenly with a 2 mol / L LiOH·H2O aqueous solution and subjected to ultrasound at 95°C for about 6 h. 0.88 Al 0.12 The sodium-lithium molar ratio of the lithium salt solution of O2 to the lithium salt solution is 1: (1-10). After the reaction is completed, the reaction system is filtered, the filter cake is washed with deionized water, and then dried at 100°C for 20 h. The collected product is O2-type LiCo 0.88 Al 0.12 O2.
[0036] The hydroxide Co prepared in this example 0.88 Al 0.12 The scanning electron microscopy morphology of (OH)2 is shown in Figure 1 The crystal nucleus is a secondary particle with a particle size of about 5 μm, which is composed of a large number of crystal chips with a particle size range of 0.1 to 0.2 μm.
[0037] Charge and discharge performance test: The test method is the same as that in Example 1. The O2-phase layered cathode material LiCo prepared in this example 0.88 Al 0.12O2 was carried out in the voltage range of 3.0-4.6 V and 0.2C, and the first charge and discharge capacities were 220 mAh / g and 210 mAh / g, respectively.
[0038] Example 3 The positive electrode material prepared in this embodiment is LiCo 0.98 Mn 0.02 O2.
[0039] A method for preparing O2-type LiCo with high exposure ratio {010} active surface 0.98 Mn 0.02 The preparation method of O2 comprises the following steps: Step 1. Coprecipitation According to the chemical formula Co 0.98 Mn 0.02 Cobalt sulfate and manganese sulfate solution are prepared in a ratio of (OH)2, wherein the molar concentration of cobalt sulfate is 3.0 mol / L, the molar concentration of NaOH solution is 4.0 mol / L, and the molar concentration of ammonia solution is 5.0 mol / L. In a nitrogen atmosphere, cobalt sulfate, manganese sulfate and NaOH are added dropwise to a reactor at a rate of 3.0 ml / min, the pH value in the reactor is controlled to be 12, the ammonia concentration in the reactor is controlled to be 0.35 mol / L, and the reaction is carried out at 45°C for 45 hours to obtain a hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor.
[0040] Step 2. High temperature calcination According to the chemical formula NaCo 0.98 Mn 0.02 O2 ratio, take Na2CO3 and the precursor Co obtained in step 1) 0.98 Mn 0.02 (OH)2, mixed evenly, pre-sintered at 500 °C for 4 h in an oxygen atmosphere, calcined at 800 °C for 10 h, and naturally cooled to room temperature to obtain a layered ordered oxide NaCo 0.98 Mn 0.02 O2.
[0041] Step 3. Ion exchange: The NaCo prepared in step 2) 0.98 Mn 0.02 O2 was mixed evenly with a 2 mol / L LiCl aqueous solution and subjected to ultrasound at a reaction temperature of 90°C for about 8 h. 0.98 Mn 0.02 The molar ratio of O2 to the sodium and lithium of the lithium salt solution is 1: (1-10). After the reaction is completed, the reaction system is filtered, and the filter cake is washed with deionized water and dried at 80 ° C for 25 h. The collected product is O2-type LiCo0.98 Mn 0.02 O2.
[0042] The hydroxide precursor Co prepared in this example 0.98 Mn 0.02 XRD of (OH)2 Figure 2 The crystallinity of the precursor is good, and the diffraction peak intensity of the {010} plane is high.
[0043] The P2 type NaCo prepared in this example 0.98 Mn 0.02 The morphology of O2 is shown in Figure 3 The length of the flaky particles is about 10 μm, the thickness is 1 to 2 μm, and the primary particles are independent of each other and do not constitute secondary particles.
[0044] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the first charge and discharge capacities of the O2 structured positive electrode material prepared in this example at a voltage range of 3.0 to 4.6 V and 1C are 225.7 mA h / g and 215.3 mAh / g, respectively.
[0045] Example 4 The positive electrode material prepared in this embodiment is LiCo 0.80 Ni 0.20 O2.
[0046] A method for preparing O2-type LiCo with high exposure ratio {010} active surface 0.80 Ni 0.20 The preparation method of O2 comprises the following steps: Step 1. Coprecipitation According to the chemical formula Co 0.80 Ni 0.20 Cobalt sulfate and nickel sulfate solutions are prepared in a ratio of (OH)2, wherein the molar concentration of cobalt sulfate is 3.0 mol / L, the molar concentration of nickel sulfate solution is 0.3 mol / L, the molar concentration of NaOH solution is 2.0 mol / L, and the molar concentration of ammonia solution is 10.0 mol / L. In a nitrogen atmosphere, cobalt sulfate, nickel sulfate and NaOH are added dropwise to a reactor at a rate of 5 ml / min, the pH value in the reactor is controlled to be 12, the ammonia concentration in the reactor is controlled to be 0.25 mol / L, and the reaction is carried out at 50°C for 40 hours to obtain a hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor.
[0047] Step 2. High temperature calcination According to the chemical formula NaCo 0.80 Ni 0.20 O2 ratio, take Na2CO3 and the precursor Co obtained in step 1) 0.80Ni 0.20 (OH)2, mixed evenly, pre-sintered at 480℃ for 4.5 h in an oxygen atmosphere, then calcined at 900℃ for 12 h, and naturally cooled to room temperature to obtain layered ordered oxide NaCo 0.80 Ni 0.20 O2.
[0048] Step 3. Ion exchange: The NaCo prepared in step 2) 0.95 Ni 0.20 O2 was mixed evenly with 5 mol / L LiCl ethanol solution and subjected to ultrasound at 80℃ for about 8 h. 0.95 Ni 0.20 The molar ratio of sodium and lithium in O2 to LiCl ethanol solution is 1: (1-10). After the reaction is completed, the reaction system is filtered, and the filter cake is washed with ethanol and dried at 90 ° C for 20 h. The collected product is O2-type LiCo 0.95 Ni 0.20 O2.
[0049] The hydroxide precursor Co prepared in this example 0.80 Ni 0.20 Scanning electron microscopy of (OH)2 Figure 4 ,From the figure, it can be seen that there are a large number of particles with a size of 0.3-0.5 μm on the particle surface, and the particle size of the secondary particles of the wafer is about 6 μm.
[0050] The hydroxide precursor Co prepared in this example 0.80 Ni 0.20 XRD of (OH)2 Figure 5 , it can be seen that the crystallinity of the precursor is good.
[0051] Charge and discharge performance test: The test method is the same as that of Example 1. The results show that the first charge and discharge capacities of the O2 structure cathode material prepared in this example at a voltage range of 3.0 to 4.6 V and 10C are 204.7 mA h / g and 201.7 mA h / g, respectively. The electrochemical curves are shown in Figure 6 .
[0052] Example 5 The positive electrode material prepared in this embodiment is LiCo 0.95 Ti 0.05 O2.
[0053] A method for preparing O2-type LiCo with high exposure ratio {010} active surface 0.95 Ti 0.05 The preparation method of O2 comprises the following steps: Step 1. Coprecipitation According to the chemical formula Co 0.95 Ti 0.05 Cobalt sulfate and sodium titanate solution are mixed in a ratio of (OH)2, wherein the molar concentration of cobalt sulfate is 2.0 mol / L, the molar concentration of sodium titanate solution is 0.5 mol / L, the molar concentration of NaOH solution is 4.0 mol / L, and the molar concentration of ammonia solution is 12.0 mol / L. In a nitrogen atmosphere, cobalt sulfate, sodium titanate and NaOH are added dropwise to a reactor at a rate of 3.0 ml / min, the pH value in the reactor is controlled to be 11.5, the ammonia concentration in the reactor is controlled to be 0.30 mol / L, and the reaction is carried out at 40°C for 35 hours to obtain a hydroxide slurry, which is then washed and dried to obtain a precursor.
[0054] Step 2. High temperature calcination According to the chemical formula NaCo 0.95 Ti 0.05 O2 ratio, take Na2CO3 and the precursor Co obtained in step 1) 0.95 Ti 0.05 (OH)2, mixed evenly, and then pre-sintered at 550 ° C for 4.5 h in an oxygen atmosphere, and then calcined at 800 ° C for 16 h, and naturally cooled to room temperature to obtain a layered ordered oxide NaCo 0.95 Ti 0.05 O2.
[0055] Step 3. Ion exchange: The NaCo prepared in step 2) 0.95 Ti 0.05 O2 was mixed evenly with a 10 mol / L LiCH3COO aqueous solution and subjected to ultrasound at 95°C for about 8 h. 0.95 Ti 0.05 The molar ratio of sodium and lithium in O2 and LiCH3COO aqueous solution is 1: (1-10). After the reaction is completed, the reaction system is filtered, and the filter cake is washed with ethanol and dried at 90 ° C for 24 h. The collected product is O2-type LiCo 0.95 Ti 0.05 O2.
[0056] The NaCo prepared in this example 0.95 Ti 0.05 The morphology of O2 is shown in Figure 7 From the figure, we can see that the length of the flake particles is about 5-6 μm, the thickness is 3-4 μm, and the primary particles are independent of each other and do not constitute secondary particles.
[0057] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the O2 structure positive electrode material LiCo prepared in this example 0.95Ti 0.05 O2 was cycled 100 times at a rate of 10C in the voltage range of 3.0-4.6 V, and the capacity retention rate was 80.0%. The cycle performance curve is shown in Figure 8 . Example 6 The positive electrode material prepared in this embodiment is LiCo 0.92 Fe 0.08 O2.
[0058] A method for preparing O2-type LiCo with high exposure ratio {010} active surface 0.92 Fe 0.08 The preparation method of O2 comprises the following steps: Step 1. Coprecipitation According to the chemical formula Co 0.92 Fe 0.08 Cobalt sulfate and ferric sulfate solution are mixed in a ratio of (OH)2, wherein the molar concentration of cobalt sulfate is 2.5 mol / L, the molar concentration of ferric sulfate solution is 0.5 mol / L, the molar concentration of NaOH solution is 2 mol / L, and the molar concentration of ammonia solution is 10.0 mol / L. In a nitrogen atmosphere, cobalt sulfate, ferric sulfate and NaOH are added dropwise to a reactor at a rate of 3.0 ml / min, the pH value in the reactor is controlled to be 11.5, the ammonia concentration in the reactor is controlled to be 0.40 mol / L, and the reaction is carried out at 45°C for 35 hours to obtain a hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor.
[0059] Step 2. High temperature calcination According to the chemical formula NaCo 0.92 Fe 0.08 O2 ratio, take Na2CO3 and the precursor Co obtained in step 1) 0.97 Fe 0.03 (OH)2, mixed evenly, pre-sintered at 550 °C for 4 h in an oxygen atmosphere, calcined at 820 °C for 25 h, and naturally cooled to room temperature to obtain layered ordered oxide NaCo 0.92 Fe 0.08 O2.
[0060] Step 3. Ion exchange: The NaCo prepared in step 2) 0.92 Fe 0.08 O2 was uniformly mixed with a 5.0 mol / L LiOH·H2O aqueous solution and subjected to ultrasound at 95°C for about 10 h. 0.92 Fe 0.08The molar ratio of sodium and lithium in O2 and LiOH·H2O aqueous solution is 1: (1-10). After the reaction is completed, the reaction system is filtered, the filter cake is washed with deionized water, and then dried at 100°C for 30 h. The collected product is O2-type LiCo 0.92 Fe 0.08 O2.
[0061] The LiCo prepared in this example 0.92 Fe 0.08 The morphology of O2 is shown in Fig. 9 From the figure, we can see that the length of the flake particles is about 4 to 5 μm, the thickness is 2 to 3 μm, and the primary particles are independent of each other and do not constitute secondary particles.
[0062] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the O2 structure positive electrode material LiCo prepared in this example 0.92 Fe 0.08 The first charge and discharge capacities of O2 at a rate of 20C in the voltage range of 3.0-4.6 V were 202.3 mA h / g and 198.5 mA h / g, respectively. The first cycle charge and discharge efficiency was 98.0%. The electrochemical curves are shown in Fig.10 .
[0063] Example 7 The positive electrode material prepared in this embodiment is LiCo 0.94 Zn 0.06 O2.
[0064] A method for preparing O2-type LiCo with high exposure ratio {010} active surface 0.94 Zn 0.06 The preparation method of O2 comprises the following steps: Step 1. Coprecipitation According to the chemical formula Co 0.94 Zn 0.06 Cobalt sulfate and zinc acetate solution are mixed in a ratio of (OH)2, wherein the molar concentration of cobalt sulfate is 1.5 mol / L, the molar concentration of zinc acetate solution is 0.6 mol / L, the molar concentration of NaOH solution is 2 mol / L, and the molar concentration of ammonia solution is 13.0 mol / L. In a nitrogen atmosphere, cobalt sulfate, zinc acetate and NaOH are added dropwise to a reactor at a rate of 4.5 ml / min, the pH value in the reactor is controlled to be 13, the ammonia concentration in the reactor is controlled to be 0.75 mol / L, and the reaction is carried out at 50°C for 35 hours to obtain a hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor.
[0065] Step 2. High temperature calcination According to the chemical formula NaCo 0.94 Zn0.06 O2. Take Na2CO3 and the precursor Co obtained in step 1) 0.94 Zn 0.06 (OH)2, mixed evenly, pre-sintered at 480℃ for 4 h in air atmosphere, calcined at 900℃ for 15 h, and naturally cooled to room temperature to obtain layered ordered oxide NaCo 0.94 Zn 0.06 O2. .
[0066] Step 3. Ion exchange: The NaCo prepared in step 2) 0.94 Zn 0.06 O2 was mixed evenly with a 5 mol / L LiCl aqueous solution and subjected to ultrasound at a reaction temperature of 90°C for about 10 h. 0.94 Zn 0.06 The molar ratio of sodium and lithium in O2 to LiCl aqueous solution is 1. After the reaction is completed, the reaction system is filtered, and the filter cake is washed with deionized water and dried at 120 ° C for 20 h. The collected product is O2-type LiCo 0.94 Zn 0.06 O2.
[0067] The LiCo prepared in this example 0.94 Zn 0.06 The scanning electron microscope morphology of O2 is as follows Fig.11 From the figure, we can see that the length of the flake particles is about 9 to 12 μm, the thickness is 0.5 to 2 μm, and the primary particles are independent of each other and do not constitute secondary particles.
[0068] Charge and discharge performance test: The test method is the same as that in Example 1. The results show that the O2 structure positive electrode material LiCo prepared in this example 0.94 Zn 0.06 The rate performance of O2 in the voltage range of 3.0 to 4.6 V is shown in Fig.12 It can be seen that the battery has a fast charge and discharge speed, and the capacity has almost no attenuation in the range of 1 to 5C. At a rate of 20C, the discharge capacity is still greater than 200 mA h / g, and the performance is stable and reliable.
[0069] The LiCo prepared in this example 0.94 Zn 0.06 O2 was cycled 50 times at a rate of 20C in the voltage range of 3.0-4.6 V, and the capacity retention rate was 76.2%. The electrochemical curve of the cycle performance is shown in Fig.13 .
[0070] In summary, the present invention achieves crystal plane regulation and effectively increases the exposure ratio of the {010} active surface by optimizing the preparation process and the composition of the O2 cobalt-based positive electrode material, thereby increasing the lithium ion diffusion channel and significantly improving the Li ⁺ Transfer dynamics greatly improve the energy density and power density of O2 cobalt-based positive electrode materials, thereby better meeting the market's requirements for high-performance lithium-ion batteries with long battery life and fast charging and discharging characteristics.
[0071] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a cobalt-based layered oxide with a high exposure ratio {010} active surface O2, characterized in that: include: Firstly, a cobalt-based hydroxide precursor is prepared by a coprecipitation method. In this process, the particle shape and size of the cobalt-based hydroxide precursor are adjusted to control the growth in the thickness direction of the wafer, thereby obtaining a cobalt-based hydroxide precursor with a large {010} crystal plane area. Then, a sodium source is introduced and a sodium-intercalated cobalt-based layered oxide is prepared by a high-temperature calcination method; Finally, the sodium-embedded cobalt-based layered oxide and lithium salt solution were subjected to a low-temperature ultrasonic liquid-phase ion exchange reaction to prepare an O2-type cobalt-based layered oxide with a high exposure ratio of {010} active surfaces.
2. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 1, characterized in that: The following steps are involved: 1) Preparation of hydroxide precursor Co by coprecipitation x M 1-x (OH)2, wherein M is Al, Ni, Mn, Ti, Fe or Zn, 0.0< x ≤ 0.2; 2) According to the chemical formula NaCo x M 1-x O2 ratio, take the sodium source and the hydroxide precursor Co prepared in step 1) x M 1-x (OH)2, mixed evenly, pre-sintered at 400-600℃ for 2-8 h in an oxygen atmosphere, then calcined at 700-1000℃ for 1-30 h, and naturally cooled to room temperature to obtain layered ordered sodium cobalt-embedded layered oxide NaCo x M 1-x O2; 3) Embedding sodium cobalt-based layered oxide NaCo x M 1-x O2 and lithium salt solution react at 80-100°C for 0.5-10 h, then filter, wash and dry to obtain high exposure ratio {010} active surface O2-type cobalt-based hierarchical oxide LiCo x M 1-x O2.
3. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 2, characterized in that: In step 1), the hydroxide precursor Co is prepared x M 1-x (OH)2, specifically including: In an inert gas atmosphere, cobalt salt, other metal salts, a precipitant and a complexing agent are added to water, the pH value of the reaction system is controlled to be 10.5-12.5, and the ammonia concentration is 0.1-1.0 mol / L; the reaction is carried out at a temperature of 40-60°C for 30-60 hours to obtain a hydroxide slurry, and the hydroxide slurry is washed and dried to obtain a precursor Co x M 1-x (OH)2.
4. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 3, characterized in that: The molar concentration of the cobalt salt is 1.0-3.0 mol / L, the precipitant is a NaOH solution with a molar concentration of 2.0-6.0 mol / L, and the complexing agent is an ammonia solution with a molar concentration of 1.0-15.0 mol / L; the drying temperature of the hydroxide slurry is 90-120°C, and the drying time is 20-30 h.
5. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 2, characterized in that: In step 2), the sodium source is selected from Na2CO3 or NaOH.
6. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 2, characterized in that: In step 2), the temperature is increased from room temperature to 400-600° C. at a heating rate of 3-10° C. / min.
7. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 2, characterized in that: In step 3), the concentration of the lithium salt solution is 0.5-10 mol / L layered oxide NaCo x M 1-x The molar ratio of O2 to sodium and lithium in the lithium salt solution is 1:(1-10); the drying temperature is 100-120°C, and the drying time is 8-25 hours.
8. The method for preparing a high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 7, characterized in that: The lithium salt solution is prepared by mixing any one of LiOH·H2O, LiCH3COO or LiNO3 with water or ethanol.
9. A cobalt-based layered oxide with a high exposure ratio {010} active surface O2 type prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The primary particles of the O2-type cobalt-based layered oxide with a high exposure ratio of {010} active surface are micrometer-sized particles, and the exposure ratio of the {010} crystal surface of the primary particles is higher than 50%.
10. Use of the high exposure ratio {010} active surface O2-type cobalt-based layered oxide according to claim 9 in preparing positive electrode materials for lithium-ion batteries.
Citation Information
Cited By
O2-type lithium ion ternary layered positive electrode material and preparation method and application thereof
CN120535032A
Triangular bipyramid vacancy layered oxide and application thereof in lithium battery
CN121292533A